Characterizing rumen microbiota and CAZyme profile of Indian dromedary camel (Camelus dromedarius) in response to different roughages - Ankit T. Hinsu (Nature Portfolio, 2021)
Abstract In dromedary camels, which are pseudo-ruminants, rumen or C1 section of stomach is the main compartment involved in fiber degradation, as in true ruminants. However, as camels are adapted to the harsh and scarce grazing conditions of desert, their ruminal microbiota makes an interesting target of study. The present study was undertaken to generate the rumen microbial profile of Indian camel using 16S rRNA amplicon and shotgun metagenomics. The camels were fed three diets differing in the source of roughage. The comparative metagenomic analysis revealed greater proportions of significant differences between two fractions of rumen content followed by diet associated differences. Significant differences were also observed in the rumen microbiota collected at different time-points of the feeding trial. However, fraction related differences were more highlighted as compared to diet dependent changes in microbial profile from shotgun metagenomics data. Further, 16 genera were identified as part of the core rumen microbiome of Indian camels. Moreover, glycoside hydrolases were observed to be the most abundant among all Carbohydrate-Active enzymes and were dominated by GH2, GH3, GH13 and GH43. In all, this study describes the camel rumen microbiota under different dietary conditions with focus on taxonomic, functional, and Carbohydrate-Active enzymes profiles.